Osteosynthesis of fifth metacarpal neck fractures with a photodynamic polymer bone stabilization system. (February 2020) - Surke, Carsten; Meier, Rahel; Haug, Luzian; Vögelin, Esther
Metacarpal neck fractures with severe displacement are commonly treated surgically with intramedullary Kirschner wires. We present the results of treatment of fifth metacarpal neck fractures using a light curable intramedullary photodynamic polymer (IlluminOss™, IlluminOss Medical Inc., East Providence, RI, USA). Twenty-nine patients with isolated displaced fifth metacarpal neck fractures were included and followed up for 12–24 weeks. All fractures had radiologically healed after 3 months. In two cases, a secondary loss of reduction was seen, which did not require further correction. During the follow-up period, range of motion of the metacarpophalangeal joint was 89% after 6 weeks and increased to 100% after 3 months compared with the uninjured side. Grip strength improved over time from 61% to 85%. No implant removal was necessary. We conclude that osteosynthesis using an intramedullary photodynamic polymer is a reliable treatment option for displaced fractures of the fifth metacarpal neck. Level of evidence: IV